Peran Rohaniwan Gereja Dalam Pendampingan Konseling Pastoral Bagi Jemaat di Gmim Tumou Tou Kendis - Kossoh, Neilly (Jurnal Ilmiah Wahana Pendidikan, 2024)
Humans have a need for mental survival. Often this mentality also influences a person's spiritual level. In responding to this need, science developed a study of the human psyche or psychology. However, the psychological approach does not touch the essence of a person's spirituality. The church exists to correct mental disorders that occur through shepherding or pastoral care. So in the field of theology, there is a study on pastoral counseling. This research uses a qualitative method with an interview and observation approach. Researchers will look at the role of clergy in understanding and implementing pastoral care at GMIM Tumou Tou Kendis. The results of this research show that clergy understand pastoral counseling as a pastoral activity as traditionally taught by the church. Then the clergy also carry out their pastoral roles intensively and on a schedule. From these two findings, it is necessary to maintain the intensity of pastoral care at GMIM Tumou Tou Kendis and develop an understanding of the nature of contemporary pastoral counseling.